Allodynia in cluster headache: a review - Leite, Elder Machado (2011)
Allodynia is defined as the experience of pain due to nonpainful stimuli, and occurs in several clinical contexts, including primary headaches. Cluster headache is a primary cephalalgia which is more common in males, characterized by excruciating pain, and autonomic trigeminal dysfunction. The prevalence of allodynia in cluster headache patients is a relevant matter with few studies devoted to. Thus, the need formore information demanded a review of most important studies to value the amount of data and its relevance. To bring light to this yet blurry matter, it was made a review using the terms "allodynia" and "cluster headache" through the CAPES periodics, accessing the most relevant studies regarding to this association.